Sea‐Ice Induced Southern Ocean Subsurface Warming and Surface Cooling in a Warming Climate. Issue 2 (6th May 2020) - Haumann, F. Alexander; Gruber, Nicolas; Münnich, Matthias
Abstract: Much of the Southern Ocean surface south of 55° S cooled and freshened between at least the early 1980s and the early 2010s. Many processes have been proposed to explain the unexpected cooling, including increased winds or freshwater fluxes. However, these mechanisms so far failed to fully explain the surface trends and the concurrent subsurface warming (100 to 500 m). Here, we argue that these trends are predominantly caused by an increased wind‐driven northward sea‐ice transport, enhancing the extraction of freshwater near Antarctica and releasing it in the open ocean. This conclusion is based on factorial experiments with a regional ocean model. In all experiments with an enhanced northward sea‐ice transport, a strengthened salinity‐dominated stratification cools the open‐ocean surface waters between the Subantarctic Front and the sea‐ice edge. The strengthened stratification reduces the downward mixing of cold surface water and the upward heat loss of the warmer waters below, thus warming the subsurface. This sea‐ice induced subsurface warming mostly occurs around West Antarctica, where it likely enhances ice‐shelf melting. Moreover, the subsurface warming could account for about 8 ± 2% of the global ocean heat content increase between 1982 and 2011. Antarctic sea‐ice changes thereby may have contributed to the slowdown of global surface warming over this period. Our conclusions are robust across all considered sensitivity cases, although the trend magnitude is sensitive to forcing uncertainties and the model's mean state. It remains unclear whether these sea‐ice induced changes are associated with natural variability or reflect a response to anthropogenic forcing. Plain Language Summary: While most of the global ocean surface has been warming in response to increasing atmospheric greenhouse‐gas concentrations, parts of the polar Southern Ocean surface have been cooling over recent decades. This cooling seems surprising, since most climate models suggest that also this region should have been warming. Using a regional ocean model, we find that the cooling can be reproduced when forcing the model with observed sea‐ice changes. Sea ice forms during the cold winter mostly along the Antarctic coast, leaving the salt that is contained in the seawater behind, and is then being pushed to the open ocean by strong winds. In the open ocean, the sea ice melts and makes the surface waters fresher there. This lateral sea‐ice transport has strengthened over recent decades, most likely due to stronger winds. In our model, the resulting freshening leads to a surface cooling, because the mixing of these waters with the warmer waters below is hindered. Thereby, the heat stays below the ocean's surface and cannot be released to the atmosphere. This retention of large amounts of heat at the subsurface possibly enhanced the melting of the Antarctic glaciers and possibly contributed to the slowdown of global warming over this period. Key Points: Sea‐ice changes explain most of the Southern Ocean surface cooling and freshening south of the Subantarctic Front between 1982 and 2011 The related strengthened surface stratification led to a subsurface warming around West Antarctica, potentially affecting ice‐shelf melt The subsurface warming contributed to the slowdown of global warming by increasing the global ocean heat content (8%) over this period